Applying the study of religions in the security domain: knowledge, skills, and collaboration. Issue 3 (2nd September 2018) - Knott, Kim
ABSTRACT: Since the 1990s, scholars of religion on both sides of the Atlantic have been drawn into engagement with law enforcement agencies and security policymakers and practitioners, particularly for their expertise on new religious movements and Islam. Whilst enabling researchers to contribute to real-world challenges, this relationship has had its frustrations and difficulties, as well as its benefits and opportunities. Drawing on examples from the UK, Canada, and the US, I set out the relationship between religion and the contemporary security landscape before discussing some of the key issues arising in security research partnerships. I then turn to the question of knowledge exchange and translation in the study of religions, developing the distinction between 'know what' (knowledge about religions and being religiously literate), 'know why' (explaining religions and making the link to security threats), and 'know how' (researcher expertise and skills in engagement with practitioners).